Des négociations entravées - Baptiste Giraud; Rémy Ponge (La Nouvelle Revue du Travail)
Understanding the modalities by means of which collective bargaining develops not only requires analysis of employers’ negotiation avoidance practices but also a review of the evisceration tactics they pursue to minimise the scope of these exchanges. Using a cross-analysis of negotiation practices in three large French companies, the text provides an account of the different ways in which employers use negotiations and how these uses are integrated into business professionals’ management strategies. This is then linked to analysis of the multiple constraints that union representatives face when adapting to new forms of economic power. Lastly, the text clarifies conditions facilitating the development of collective bargaining in large companies as well as the constraints limiting their impact.